Doll bones - Black, Holly (New York : Margaret K. McElderry Books, 2013)
Zach, Alice, and Poppy, friends from a Pennsylvania middle school who have long enjoyed acting out imaginary adventures with dolls and action figures, embark on a real-life quest to Ohio to bury a doll made from the ashes of a dead girl.
School Library Journal starred, June 2013
Booklist starred, March 2013
Bulletin of the Center for Children's Books starre, June 2013
Pub Weekly, March 2013
Kirkus Starred, March 2013
New York Times, June 2013
Keywords: Friendship -- Juvenile fiction; Dolls -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Friendship -- Fiction; Dolls -- Fiction; Ghosts -- Fiction; Family problems -- Fiction; Adventure and adventurers -- Fiction; Friendship -- Fiction; Dolls -- Fiction; Ghost stories; Family problems -- Fiction; Adventure fiction; Ghost stories; Adventure fiction